PREPARATION, CHARACTERIZATION, AND IN VITRO EVALUATION OF GEL CONTAINING NANOPHYTO-PHOSPHOLIPID COMPLEX OF KOPASANDA LEAF EXTRACT (CHROMOLAENA ODORATA (L.) R. M. KING AND H. ROB) - RIDWAN, SUCILAWATY; WAHYUNI, NURUL; PASARIBU, GUNAWAN; SAFWAN, SAFWAN; HAJRIN, WAHIDA; FITRIANA, MARIAMA; ROIYAN, KAMELIA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to prepare, characterize, and in vitro evaluation of the gel containing nanophyto-phospholipid complex of kopasanda leaf extract. Methods: Kopasanda dried leaf was extracted by extraction reflux method, followed by total phenolic content of extract measurement using Spectrophotometry UV-Vis method. The nanophyto-phospholipid complex was prepared using an antisolvent evaporation method with various ratios between extract and phospholipid of 1:1; 1:2; 1:3. The optimum ratio was evaluated by entrapment efficiency (%). The nanophyto-phospholipid complex formation was characterized by polydispersity index, particle size, Fourier Transform Infra-Red (FT-IR), and the Transmission Electron Microscope (TEM) method. The optimum nanophyto-phospholipid complex was formulated into gel preparation. The in vitro permeation study was performed to discover the influence of gel containing nanophyto-phospholipid complex compared with gel-containing extract without the nanophyto-phospholipid complex formation. Results: Thetotal phenolic content of kopasanda leaf extract was 117.214±3.054 mg/GAE. The optimum ratio of kopasanda leaf extract and phospholipid was 1: 2 with entrapment efficiency (%), particle size, and polydispersity index equal to 99.897±0.001%, 130.1 nm and 0.394. The morphology of the nanophyto-phospholipid complex was spherical and the complex formation was confirmed by the FTIR spectrum. The permeation test showed that the gel containing nanophyto-phospholipid complex had better diffusion than the gel without the nanophyto-phospholipid complex formation. Conclusion: The gel containing nanophyto-phospholipid complex formation exhibited the potential drug delivery system to increase the phenolic content permeation of kopasanda leaf extract.